Cognitive impairment and depression precede increased HDL-C levels in middle-aged and older Chinese adults: cross-lagged panel analyses - Yi-Hui Liu; Mu-Tong Chen; Yong-Yi He; Ming Chen; Jia-Rong Liang; Fu-Jun Jia; Quan Huang; Rui Zhou; Cai-Lan Hou (Lipids in Health and Disease, 2024)
Abstract Background High-density lipoprotein cholesterol (HDL-C) is widely recognized for its protective effects against cognitive decline. However, recent studies have presented conflicting results, with some suggesting no significant cognitive benefits or even an increased risk of dementia associated with high HDL-C levels. For those who suffer from depression, the cognitive benefits of HDL-C may be diminished or reversed. The purpose of this study is to investigate the associations between HDL-C, cognitive ability, and depressive symptoms in middle-aged and older Chinese adults. Methods The datasets utilized were sourced from the China Health and Retirement Longitudinal Study (CHARLS) for the years 2011 and 2015, comprising 4,302 participants. Cross-lagged models were employed to explore the temporal sequence between cognitive performance and HDL-C levels, and to examine the interplay among depression, cognition, and HDL-C. Confounding factors such as sociodemographic characteristics, sleep conditions, and history of chronic diseases were controlled for. Results The analysis revealed unidirectional effects of baseline impaired cognition and greater severity of depression on increased HDL-C levels at follow-up (β =  − 0.036 and β = 0.028, respectively, P < 0.05). However, higher baseline HDL-C levels did not significantly predict cognitive performance or depression 4 years later (β =  − 0.008 and β = 0.023, respectively, P > 0.05). Depressive symptoms and cognition were found to have a significant bidirectional association (β =  − 0.026 and β =  − 0.053, respectively, P < 0.05). Conclusions Cognitive impairment and depression are associated with higher HDL-C levels, whereas higher HDL-C levels do not appear to protect against cognitive decline or depressive symptoms. These findings underscore the importance of preserving cognitive and mental health, which may lower the likelihood of cardiovascular disease and dementia. Future studies should validate these findings and develop targeted interventions tailored to specific populations.